The role of local ablative therapy in oligometastatic non-small-cell lung cancer: hype or hope. (December 2016) - Bansal, Pranshu; Rusthoven, Chad; Boumber, Yanis; Gan, Gregory N
In recent years, the emergence of the oligometastatic state has called into question whether patients found to have a limited or low metastatic tumor burden may benefit from locally ablative therapy (LAT). In the past two decades, stereotactic body radiation therapy has been increasingly used to safely deliver LAT and provide high local control in nonoperable non-small-cell lung cancer patients. Mostly retrospective analyses suggest that using LAT for oligometastatic disease in non-small-cell lung cancer offers excellent local control and may provide an improvement in progression-free survival. Any meaningful improvement in cancer-specific survival remains debatable. We examine the role of integrating LAT in this patient population and the rationale behind its use in combination with targeted therapy and immunotherapy.